Majority of the erythrocyte binding proteins of the Pvfam “a” family of Plasmodium vivax interact with Basigin to assist parasite entry into the host cell - Manish Tripathi; Meghna Santoshi; Yagya D. Sharma; Sumit Rathore (Frontiers in Cellular and Infection Microbiology)
Molecular mechanisms of red cell invasion by the Plasmodium vivax parasite remain obscure since information on receptor–ligand interaction is scarce. Several proteins of the P. vivax Pvfam “a” family are known to bind with host erythrocytes. Some of them share their erythrocyte receptors with each other and vice versa, but the identification of these receptors is awaited with the exception of PvTRAg38. Here, we demonstrate by using solid-phase binding assay and surface plasmon resonance that majority (7 out of 10) of these erythrocyte binding proteins (PvTRAg, PvTRAg33.5, PvTRAg35.2, PvTRAg34, PvTRAg36, PvTRAg38, and PvTRAg69.4) interact with the erythrocyte receptor Basigin. These interactions seem to be important for the parasite’s survival since each of these proteins interfered with the parasite’s growth in a heterologous culture system. Furthermore, a higher parasite growth inhibition rate was observed with the combination of these proteins, suggesting the significance of multiple parasite ligand’s interaction with the same erythrocyte receptor during the invasion process. These results will be helpful in understanding P. vivax biology and developing the therapeutics for vivax malaria.